Cerebral Blood Volume During Neonatal Transition in Term and Preterm Infants With and Without Respiratory Support - Schwaberger, Bernhard; Pichler, Gerhard; Binder-Heschl, Corinna; Baik-Schneditz, Nariae; Avian, Alexander; Urlesberger, Berndt (Frontiers in Pediatrics, 2018)
Background: Recently, we demonstrated that in healthy newborn infants cerebral blood volume (CBV) was decreasing continuously after birth. We hypothesized that this was due to the increase in oxygen delivery to the brain during neonatal transition. Thus delayed cerebral oxygen delivery in infants in need for respiratory support (RS) during postnatal stabilization might influence changes in CBV. Objective: Aim of the study was to evaluate transitional changes in CBV immediately after birth in term and preterm infants with and without need of RS. Methods: We performed a post-hoc analysis of data collected as primary and secondary outcome parameters in prospective observational studies and randomized controlled trials at the Medical University of Graz (Austria). NIRS measurements by using 'NIRO 200-NX' (Hamamatsu, Japan) were carried out over the first 15 min after birth in term and preterm infants delivered by cesarean section with and without requirement for RS. Results: In 204 neonates, we observed a significant decrease in CBV within the first 15 minutes after birth (p < .001) with a trend toward smaller ΔCBV in neonates receiving RS (p = .097) compared to neonates without RS. Differences of ΔCBV between groups reached statistically significance (p < 0.05) at minutes 2, 6 and 7, and showed a trend (p <0.1) at minutes 3, 4 and 5. After adjusting for gestational age, these differences became smaller and failed to reach significance. Conclusions: We observed a significant decrease of CBV in term and preterm infants with and without RS. Interestingly, ΔCBV was smaller in the first seven minutes in neonates with RS reaching statistically significance (p < .05) at minutes 2, 6 and 7. This study cannot differentiate, whether RS itself or the condition leading to requirement for RS is responsible for the observed CBV behavior.